Secular trend in body hight and weight of children from Gdańsk - Berdychowski, Włodzimierz (Anthropological Review, 1978)
Results of examinations carried in 1959, 1966 and 1975 on children aged 7-14 years living in the Gdańsk City are compared. Both body height and weight of comparable age groups had increased between 1959 and 1975. Moreover in the period 1959 - 1966 relative (to the height) body weight has increased.